Molecular MRI using exogenous enzymatic sensors and endogenous chemical exchange contrast - Taylor, Alexander John (2016)
Molecular magnetic resonance imaging (MRI) methods have the potential to provide detailed information regarding cellular and molecular processes at small scales within the human body. Nuclear signals from chemical samples can be probed using specialised MRI techniques, to highlight molecular contrast from particular enzymes or metabolites. The aim of the work described in this thesis is to investigate both exogenous and endogenous contrast mechanisms using fluorine MRI and chemical exchange saturation transfer (CEST) respectively, in order to detect molecular changes in vitro.